2009
DOI: 10.1115/1.3058681
|View full text |Cite
|
Sign up to set email alerts
|

The Equivalent Depth of Wave-Induced Scour Around Offshore Pipelines

Abstract: Physical experiments have been conducted to study the scouring around a pipe over an erodible bed under wave motion. The results show that the depth of the wave-induced scour is reduced when the pipe is installed in a primary depth. It is also indicated that when the primary installation depth of the pipe, |e|, exceeds a specified depth, no scouring occurs underneath the pipe. This specific depth is called the equivalent depth of wave-induced scour, Se. The equivalent depth of wave-induced scour is estimated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Mousavi et al [27] proposed the following equation in live bed condition, based on their experiments for the wave-induced scour depth around pipelines:…”
Section: Scour Around Submarine Pipelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mousavi et al [27] proposed the following equation in live bed condition, based on their experiments for the wave-induced scour depth around pipelines:…”
Section: Scour Around Submarine Pipelinesmentioning
confidence: 99%
“…They found that ANN-based model is more accurate than the previous empirical equations. Hereafter, Lucassen [6], Sumer and Fredsøe [7], Pu et al [8] and Mousavi et al [27] are referred to as Lu, SF, Pe and Me, respectively.…”
Section: Scour Around Submarine Pipelinesmentioning
confidence: 99%
“…Flow around pipelines in a steady current and under waves has been investigated extensively in the past few decades. Some of these studies are; Chao and Hennesy (1972), Kjeldsen et al (1973), Bijker and Leeuweistein (1984), İbrahim andNalluri (1986), Mao (1986), Sumer and Fredsøe (1990), Sumer and Fredsøe, (1996), Klomp et al (1996), Cevik and Yuksel (1999), Mousaviet et al (2009), Yasa (2011) and Kızıloz et al (2013). Numerical methods and other computing tools have been developed to simulate scour around submarine pipelines by Liang and Cheng (2005a), Liang and Cheng (2005b).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, several experimental studies on wave-induced scour beneath pipelines have been carried out (e.g. Mao 1986;Sumer and Fredsøe 1990;Mousavi et al 2009;Xu et al 2010). Sumer and Fredsøe (1990) pointed out that the equilibrium scour depth for live bed conditions is governed by Keulegan-Carpenter number, KC, defined as:…”
Section: Introductionmentioning
confidence: 99%